Philo of Alexandria and post-Aristotelian philosophy - Alesse, Francesca. (Studies in Philo of Alexandria, 2008)
The essays collected in this volume focus on the role played by the philosophy of the Hellenistic, or post-Aristotelian age (from the school of the successors of Aristotle, Theophrastus and other Peripatetics, Epicurus, Sceptical Academy and Stoicism, to neo-Pythagorenism and the schools of Antiochus and Eudorus) in Philo of Alexandria's works. Despite many authoritative studies on Philo's vision of Greek philosophy as an exegetical tool in allegorizing the Scripture, there is not such a comprehensive overview in Philo's treatises that takes in account both the progress achieved in the recent interpretation of Hellenistic philosophy and analysis of ancient doxographical literature.